PROGRAM KIRIBATI AUSTRALIA NURSING INITIATIVE DALAM MENDUKUNG KEBIJAKAN MIGRATION WITH DIGNITY PEMERINTAH KIRIBATI 2006 - 2014 - Indira Santi, Ni Made; Dharmiasih, D.A. Wiwik; Kumala Dewi, Putu Ratih (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2015)
ABSTRAK Kiribati is a small country with low lying islands that is in danger of being completely flooded within 60 years because of the rising sea level. It has been predicted that the islands of Kiribati will not inhabitable anymore in 30 years from now. Despite of the environmental problems, Kiribati is also encountering an extreme poverty and unemployment problems. The iKiribati have no choice but to migrate to another before Kiribati becomes uninhabitable. The government of Kiribati has announced a policy called “migration with dignity” to prepare the migration of iKiribati. Australia help Kiribati by granting a scholarship program to iKiribati which allows them to study nurse in Australia. This research is concerned with how the KANI’s program could help prepare iKiribati migrate by using the Human Capital Theory and the foreign aid concept. Key words: migration with dignity, human capital, migration, and foreign aids.